A deeply conserved, noncanonical miRNA hosted by ribosomal DNA - Lai, Eric C. (2015)
Advances in small RNA sequencing technologies and comparative genomics have fueled comprehensive microRNA (miRNA) gene annotations in humans and model organisms. Although new miRNAs continue to be discovered in recent years, these have universally been lowly expressed, recently evolved, and of debatable endogenous activity, leading to the general assumption that virtually all biologically important miRNAs have been identified. Here, we analyzed small RNAs that emanate from the highly repetitive rDNA arrays of Drosophila. In addition to endo-siRNAs derived from sense and antisense strands of the pre-rRNA sequence, we unexpectedly identified a novel, deeply conserved, noncanonical miRNA. Although this miRNA is widely expressed, this miRNA was not identified by previous studies due to bioinformatics filters removing such repetitive sequences. Deep-sequencing data provide clear evidence for specific processing with precisely defined 5′ and 3′ ends. Furthermore, we demonstrate that the mature miRNA species is incorporated in the effector complexes and has detectable trans regulatory activity. Processing of this miRNA requires Dicer-1, whereas the Drosha–Pasha complex is dispensable. The miRNA hairpin sequence is located in the internal transcribed spacer 1 region of rDNA and is highly conserved among Dipteran species that were separated from their common ancestor ∼100 million years ago. Our results suggest that biologically active miRNA genes may remain unidentified even in well-studied organisms.